Učestalost simptoma distresa u populaciji studenata medicine i njihova povezanost sa simptomima poremećaja pažnje i hiperaktivnosti - Joković, Nikola; Kojović, Natalija; Mandić Maravić, Vanja; Marić Bojović, Nađa (Medicinski podmladak, 2024)
Introduction: Studies have indicated that symptoms of depression and anxiety are more prevalent in students than in the general population, and even more prevalent among students with pronounced symptoms of attention deficit hyperactivity disorder (ADHD). ADHD is most commonly diagnosed in childhood, but there is cumulative evidence of its presence in adults as well. No studies have been conducted on the student population in Serbia thus far.Material and Methods: The study was conducted on 404 students of the Faculty of Medicine, University of Belgrade, with an average age of 21.8±1.9 years, of which 78.7% were female. The assessment included the Adult ADHD Self-Report Scale (ASRS v1.1), Patient Health Questionnare-9 (PHQ-9), General Anxiety Disorder-6 (GAD-6) and Patient Health Questionnare-4 (PHQ-4) self-report scales and a questionnaire for socio-demographic, psychotropic drug use, and heredity of ADHD.Results: In this sample, 6.4% of students had severe depressive symptoms, while 9.6% had symptoms of severe anxiety. ADHD-screening positive students had significantly more pronounced symptoms of depression, anxiety and distress compared to other students (p
Keywords: English